Profile and outcomes of children presenting with infection-related glomerulonephritis - Kalra, Lt Col Suprita; Jain, Maj Gitanjali; Panda, Lt Col Sanjay Kumar; Narayan, Col Venkat K (Indian Journal of Child Health, 2018)
Poststreptococcal acute glomerulonephritis (PSGN) was reported as the most common cause of GN in children. There has been, however, a marked shift in epidemiology in recent years with the decline in poststreptococcal cases. Various other bacteria and rarely viral and fungal infections are associated with GN. More cases are now being reported with ongoing infection at the time GN is diagnosed. Therefore, the term infection-related GN (IRGN) is now being used increasingly. We describe the clinical profile and outcomes of children presenting with IRGN at a tertiary care center in the past 1 year. 5 children presented with features of GN. Only 1 of the 5 had the course typically described in PSGN. Two patients also had a post-infectious course but with some unusual features. Another patient had an ongoing systemic infection in the form of pneumonia at the time of onset of features GN, while our fifth patient developed an infection-related GN with dengue illness.